Modern pedagogical technologies as a means of developing oral speech of students in national classes - Jumabaeva, Fariyda Qaniyarovna (The Lingua Spectrum, 2026)
The article examines the problem of developing oral speech among students of national classes through the use of modern pedagogical technologies in Russian language lessons. The relevance of the research is обусловлена the necessity of improving students’ communicative competence in conditions of a limited Russian-speaking environment. The purpose of the study is to analyze the effectiveness of interactive teaching methods in the process of forming oral speech skills. The research employed methods of pedagogical observation, comparative analysis, experimental teaching, and diagnostics of students’ speech activity. The experimental work was conducted among 6–8 grade students of secondary school №42 in the Chimbay district. The article analyzes the use of role-playing games, digital technologies, group activities, discussions, and creative speech-development methods. The results of the study demonstrated that the systematic implementation of modern pedagogical technologies contributes to increasing students’ speech activity, expanding vocabulary, reducing grammatical and phonetic mistakes, and developing sustainable motivation for learning Russian